ANALISIS KRITIS PROGRAM PENGELOLAAN DANA ZAKAT DAN INFAK DALAM MEMBENTUK MODAL SOSIAL MASYARAKAT - Nairatul Ahkamiyah; Suherman Rosyidi (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
The existence of religious institutions has a positive relationship with the strengthening of social capital and improving the welfare of poor community. The religious institution that is the subject of this research is the Tebuireng Pesantren Social Institution (LSPT). This research aims to analyze the management program of zakat funds and infak by LSPT in shaping socialcapital of the surrounding communities. The research method used in this research is descriptive qualitative.Through the PMM program and the griya dakwah program, LSPT forms social capital. The PMM program has been able to shape the social capital of the poor community, but has not been fully successful. Main job Griya dakwah program is to launch someone who is an expert in related field to preach in Ngimbang community. The main activity of the griya dakwah program is routine study every friday night, the study further strengthens social capital in the Ngimbang community  REFERENCESAfifuddin, dan Beni Ahmad S. 2012. Metodologi Penelitian Kualitatif. Bandung: CV. Pustaka Setia.Al Ghaziy, Muhammad bin Qasim. 2005. Fathul Qarib Al-Mujib. Jeddah. Al-Haramain.Agustin, Atut Firda, Khusnul Ashar dan Multifiah. 2013. Identifikasi Modal Sosial pada Program Pemberdayaan Masyarakat Miskin Melalui Dana Zakat, Infak dan Sedekah. (Online) (ejournal.uin-malang.ac.id, diakses pada 12 April 2017).Al Qurthubi, Syaikh Imam.2007. Al-Jami’ Li Ahkᾱmi ‘l-Qurἅn. Vol 3. Jakarta: Pustaka Azzam.Badan Amil Zakat Nasional. 2017. Tugas Pokok Baznas. Jakarta: BAZNAS.Binjai, Abdul Halim Hasan. 2011. Tafsir Al Ahkam. Jakarta: Prenada Media Group.Chaudhry, Muhammad Syarif. 2016. Prinsip Dasar Sistem Ekonomi Islam. Jakarta: Prenada Media GroupField, John. 2010. Modal Sosial. Bantul: Kreasi Wacana.Hafidhuddin, Didin. 2008. Panduan Praktis tentang Zakat, Infak, dan Sedekah. Jakarta: Gema InsaniHamim, Nur Ifan. 2016. Manajemen Pengelolaan Infaq di Lembaga Sosial Pesantren Tebuireng (Tinjuan Teori Manajemen George Terry). Skripsi tidak diterbitkan. Malang Universitas Islam Negeri Maulana Malik Ibrahim Malang.Handoyo, Eko. 2013.  Kontribusi Modal Sosial dalam Meningkatkan Kesejahteraan Pedagang Kaki  Lima Pascarelokasi. Jurnal Komunitas, 5 (2): 252-266 https://almanhaj.or.id (online) diakses pada 20 Juli 2017https://tebuireng.online/yayasan-hasyim-asyari/ (online) diakses pada 11 Juli 2017http://pusat.baznas.go.id(Online) diakses pada 12 April 2017Kearns, Ade. 2004. Social Capital, Regeneration & Urban Policy. CNR Paper 15.Mahalli, Ahmad Mudjab. 2004. Hadits-hadits Muttafaq `Alaih: Bagian Ibadat. Jakarta: Prenada Media Group.Mahalli, Ahmad Mudjab dan Ahmad Rodli Hasbullah. 2004. Hadits-hadits Muttafaq `Alaih: Bagian Munakahat dan Mu’amalat. Jakarta: Prenada Media Group.Mardani. 2012. Ayat-ayar dan Hadits Ekonomi Syariah. Edisi Pertama. Jakarta: Rajawali PersMuhammad. 2011. Manajemen Organisasi Zakat. Malang: Madani.Mustafa, Edwin Nasution dkk (Eds). 2009. Indonesia Zakat & Development Report 2009. Depok: PEBS dan CIDNasution, Ahmadriswan, Ernan Rustiadi, Bambang Juanda dan Setia Hadi. 2014. Dampak Modal Sosial terhdap Rumah Tangga Perdesaan di Indonesia. Vol.30. Mimbar, 2: 137-148Qardawi, Yusuf. 1999. Hukum Zakat. Bandung: PT Pustaka Mizan.Quthb, Sayyid. 2000. Tafsir Fi Zhilalil Qur`an: Di Bawah Naungan Al-Qur`an. Jilid 1. Jakarta: Gema Insani.Robison, Lindon J, Marcelo E.S and A. Allan S. 2002. Social Capital and Poverty Reduction:Toward to Mature Paradigm. Agricultural Economic Report, 614: 1-50.Sanrego, Yulizar D dan Moch Taufik. 2016. Fiqh Tamkin (Fiqih Pemberdayaan). Jakarta: Qisthi Press Setkab.go.id (Online) diakses 12 April 2017Shihab, M.Quraish. 2002. Tafsir Al-Mishbah: pesan, kesan, dan keserasian Al-Qur`an. Vol 1. Jakarta: Lentera Hati.-----------------------. 2002. Tafsir Al-Mishbah: pesan, kesan, dan keserasian Al-Qur`an. Vol 3. Jakarta: Lentera Hati-----------------------. 2002. Tafsir Al-Mishbah: pesan, kesan, dan keserasian Al-Qur`an. Vol 8. Jakarta: Lentera Hati-----------------------. 2002. Tafsir Al-Mishbah: pesan, kesan, dan keserasian Al-Qur`an. Vol 12. Jakarta: Lentera Hati------------------------. 2002. Tafsir Al-Mishbah: pesan, kesan, dan keserasian Al-Qur`an. Vol 13. Jakarta: Lentera Hati.Sugiono. 2013. Memahami Penelitian Kualitatif. Bandung: Alfabeta.Suharto, Edi. 2008. Modal Sosial dan Kebijakan Publik. http://www.policy.hu/suharto(Online) diakses pada 19 Juli 2017Supono, Boedyo. 2011. Peranan Modal sosial dalam Implementasi Manajemen dan Bisnis. Vol 11. Jurnal Ekonomi dan Kewirausahaan,1: 10-16Syahra,  Rusydi. 2003. Modal Sosial: Konsep dan Aplikasi. Vol 5. Jurnal Masyarakat dan Budaya, 1: 1-22Syahyuti. 2008. Peran Modal Sosial (Social Capital) dalam Perdagangan Hasil Pertanian. Vol 26.  Forum Penelitian Agro Ekonomi, 1: 32-43Widayani, Retno dan Nisa Agistiani Rachman. 2013. Studi Kemunculan Modal Sosial. Vol 17.  JKAP, No 2: 1-75Widiastuti, Tika. 2013. Pengaruh Kepatuhan Berzakat terhadap Kinerja BAZ dan Non-BAZ Serta Kesejahteraan Mustahiq si Jawa Timur. Disertasi tidak diterbitkan. Surabaya Pascasarjana Universitas Airlangga Surabaya.Wahid, Salahuddin. 2011. Transformasi Pesantren Tebuireng. Malang: UIN Maliki press.Yin, Robert K. 2003. Studi Kasus : Desain dan Metode. Jakarta: PT. Raja Grafindo Persada.Yin, Robert K.2014.Case Study Research: Design and Methods. Fifth edition. America: SAGEYunus, Mahmud. 1990. Kamus Arab-Indonesia. Jakarta: PT. Hidakarya Agung.